2023
DOI: 10.3389/fphys.2023.1111404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of demand-feeding and dietary protein level on nitrogen metabolism and symbiont dinitrogen gas production of common carp (Cyprinus carpio, L.)

Abstract: Ammonia accumulation is a major challenge in intensive aquaculture, where fish are fed protein-rich diets in large rations, resulting in increased ammonia production when amino acids are metabolized as energy source. Ammonia is primarily excreted via the gills, which have been found to harbor nitrogen-cycle bacteria that convert ammonia into dinitrogen gas (N2) and therefore present a potential in situ detoxifying mechanism. Here, we determined the impact of feeding strategies (demand-feeding and batch-feeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 44 publications
0
9
1
Order By: Relevance
“…This study is, to our knowledge, the first in which the effect of feeding regime on the gut microbial community is combined with individual physiological parameters. We hypothesised that demand feeding would affect gut microbiota composition to a larger extent than dietary protein content, in line with its effects on fish physiology found in the study with the same carp (Mes et al, 2023). We additionally hypothesised that microbial associations in the gut microbiota were affected by demand feeding.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…This study is, to our knowledge, the first in which the effect of feeding regime on the gut microbial community is combined with individual physiological parameters. We hypothesised that demand feeding would affect gut microbiota composition to a larger extent than dietary protein content, in line with its effects on fish physiology found in the study with the same carp (Mes et al, 2023). We additionally hypothesised that microbial associations in the gut microbiota were affected by demand feeding.…”
Section: Discussionmentioning
confidence: 67%
“…In our previous study using the same carp, we found significant effects of demand feeding on specific growth rates and hepatic and intestinal GDH activities (Mes et al, 2023). Here, we determined if these individual physiological parameters could explain variations in gut microbiota composition.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations